p73 Is Required for Ovarian Follicle Development and Regulates a Gene Network Involved in Cell-to-Cell Adhesion - Gabriela L. Santos Guasch (iScience, 2018)
Summary: We report that p73 is expressed in ovarian granulosa cells and that loss of p73 leads to attenuated follicle development, ovulation, and corpus luteum formation, resulting in decreased levels of circulating progesterone and defects in mammary gland branching. Ectopic progesterone in p73-deficient mice completely rescued the mammary branching and partially rescued the ovarian follicle development defects. Performing RNA sequencing (RNA-seq) on transcripts from murine wild-type and p73-deficient antral follicles, we discovered differentially expressed genes that regulate biological adhesion programs. Through modulation of p73 expression in murine granulosa cells and transformed cell lines, followed by RNA-seq and chromatin immunoprecipitation sequencing, we discovered p73-dependent regulation of a gene set necessary for cell adhesion and migration and components of the focimatrix (focal intra-epithelial matrix), a basal lamina between granulosa cells that promotes follicle maturation. In summary, p73 is essential for ovarian folliculogenesis and functions as a key regulator of a gene network involved in cell-to-cell adhesion and migration. : Molecular Network; Functional Aspects of Cell Biology; Developmental Biology; Omics Subject Areas: Molecular Network, Functional Aspects of Cell Biology, Developmental Biology, Omics